Selected Determinants of Job Satisfaction among Special Needs Educators for the Learners with Hearing Impairement in Special Schools; A Case Study of Kakamega County-Kenya - Nyongesa, Gregory Jumah (JOOUST, 2020)
Effective teaching and learning to achieve the educational goals require satisfied teachers, yet, most of the teachers in Kenya indicate lack of job satisfaction with their work. The rising numbers of special needs educators exiting from special schools for the Hearing Impaired and the frequent strikes are the possible indicators. This study examined the selected determinants of Job Satisfaction among Special Needs Educators for the Learners with Hearing Impairment in Special Schools in Kakamega County-Kenya. The study was guided by four objectives: To establish the influence of Compensation on teacher Job Satisfaction among Special Needs Educators for the Learners with Hearing Impairment in Special Schools, to determine the influence of working conditions on the teacher Job Satisfaction among Special Needs Educators for the Learners with Hearing Impairment in Special Schools, to examine the role of recognition on teacher Job Satisfaction among Special Needs Educators for the Learners with Hearing Impairment in Special Schools and to assess the role of training on Job Satisfaction among Special Needs Educators for the Learners with Hearing Impairment in Special Schools. This study employed the Two Factor Theory of Herzberg and adopted multiple case study design. The study was conducted in Special Primary Schools for the HI in Kakamega County. The target population was 59 informants, same as sample size, which comprised of four headteachers, four deputy headteachers, 4 7 classroom teachers and three curriculum support officers for special needs drawn from each of the sub counties where the special primary schools for the HI is located. The sample size was a total of 58 participants. Purposive and Saturated sampling techniques were used. Interview schedules, focus group discussions and document analysis guide were used for data collection. The study adopted thematic analysis to generate the findings. The study found out that Special Needs Educators were not satisfied with the salary and allowances that they were given by the Teachers Service Commission (TSC).lt was also importantly noted that not all the special needs educators who are deployed in the special schools for the learners with HI earn the special duty allowance. On the other hand, Fringe benefits and incentives are highly valued by the special needs educators for the learners with HI. With reference to working conditions, many of the special needs educators were not satisfied with the working conditions that the schools had. The workload for the special educators in some schools was unattainable. Some schools had teachers taking as high as 46 lessons per week. The study revealed that all the special needs educators were dissatisfied with the promotion. Training was also another factor that influenced special educators job satisfaction. Special educators acknowledged that they value workshops, seminars and inset programs. The study concluded that training influences less for job satisfaction compared to other factors. It was recommended that the government should improve the remuneration of the special educators for the hearing impaired.